One-step Synthesis of Stable, Nontoxic, Orange Quantum Dots Fluorescent Powder - Shuhong Xu; Jin Shen; Zhaochong Wang; Jinhua Du; Chunlei Wang; Zengxia Zhao; Yiping Cui (Nanomaterials and Nanotechnology)
Stable, nontoxic, and aqueous Cu:ZnInSe quantum dots (QDs) have been synthesized using one-step method. Through controlling pH, the amount of 3-mercaptopro‐ pionic acid (MPA), and impurities Cu and In, high-quality Cu:ZnInSe QDs have been obtained. First, as-prepared Cu:ZnInSe QDs have better thermal stability. The photolu‐ minescence (PL) intensity and wavelength are not changed during long-time heating reflux. Besides, the synthesizing method is simple, and raw materials are green. Cu:ZnInSe QDs are perfect fluorescent powder.